Desperately seeking (environmental) Kuznets: A new look at the evidence - Marzio Galeotti; Alessandro Lanza; Francesco Pauli (Fondazione Eni Enrico Mattei (FEEM), 2001)
The number of studies seeking to empirically characterize the reduced-form relationship between a country economic growth and the quantity of pollutants produced in the process has recently increased significantly. In several cases researchers have found evidence pointing to an inverted-U "environmental Kuznets" curve. In the case of a major greenhouse gas, CO2, however, the evidence is at best mixed. This paper attempts to shed further light on this issue by using a newly developed dataset on emissions and by employing a new highly flexible functional form.
Keywords: O13; Q30; Q32; C12; C23; 330; Environment; growth; CO2 emissions; panel data; Wirtschaftswachstum; Umweltbelastung; Treibhausgas-Emissionen; Schätzung; OECD-Staaten; Entwicklungsländer; Environmental Kuznets Curve